Dampak Work from Home, Work from Office dan Hybird Working terhadap Motivasi Kerja Karyawan - Dara Suzana; Harlyn L Siagian (Journal of Telenursing (JOTING), 2022)
This study aims to determine the impact of work from home, work from office and hybrid working on work motivation. The method used is the descriptive quantitative method. The results showed that the t-value of work from home was 2.451 (>1.65978), work from office was 1.179 (>1.65978) and hybrid working was 1.774 (>1.65978). The fcount value obtained is 2,964 (>2.70). In conclusion, work from home, work from office and hybrid working positively and significantly impact employee motivation. Keywords: Hybrid Working, Work Motivation, Work from Home, Work from Office